Integrated Methodologies for the 3D Survey and the Structural Monitoring of Industrial Archaeology: The Case of the Casalecchio di Reno Sluice, Italy. (7th July 2011) - Bitelli, Gabriele; Gatta, Giorgia; Girelli, Valentina Alena; Vittuari, Luca; Zanutta, Antonio
Abstract : The paper presents an example of integrated surveying and monitoring activities for the control of an ancient structure, the Casalecchio di Reno sluice, located near Bologna, Italy. Several geomatic techniques were applied (classical topography, high-precision spirit levelling, terrestrial laser scanning, digital close-range photogrammetry, and thermal imagery). All these measurements were put together in a unique reference system and used in order to study the stability and the movements of the structure over the period of time observed. Moreover, the metrical investigations allowed the creation of a 3D model of the structure, and the comparison between two situations, before and after the serious damages suffered by the sluice during the winter season 2008-2009. Along with the detailed investigations performed on individual portions of the structure, an analysis of the whole sluice, carried out at a regional scale, was done via the use of aerial photogrammetry, using both recently acquired images and historical photogrammetric coverage. The measurements were carried out as part of a major consolidation and restoration activity, carried out by the "Consorzio della Chiusa di Casalecchio e del Canale di Reno".